2008
DOI: 10.14723/tmrsj.33.161
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial electron transfer mechanisms in bithiophene sensitized TiO2 based solar cells

Abstract: Kinetic studies at Ti0 2 /bithiophene/electrolyte interfaces were conducted, and their parameters to the solar cell functions were related. The solar cell based upon the bithiophene sensitised Ti0 2 films resulted in the maximum IPCE of approximately 25 % at 400 nm. Comparison of emission studies between the bithiophene adsorbed Ti0 2 and Alz0 3 revealed the electron injection from the excited bithiophene into the Ti0 2 with the efficiency of nearly 100 %. The charge recombination between the bithiophene catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The measurements were repeated for three different samples on each CdS coating. Submicrosecond to millisecond transient absorption studies were conducted by a home-built transient absorption spectrometer with a Nd/YAG laser (Spectra Physics, Quanta-Ray GCR-11) pumped dye laser (Usho Optical Systems, DL-100, ∼10 ns pulse duration) as a pump source, a 100 W tungsten lamp as a probe source, a photodiode-based detection system (Costronics Electronics), and a TDS-2022 Tektronix oscilloscope . All transient data were collected by confirming identical excitation homogeneity and density of absorbed photons for all samples.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were repeated for three different samples on each CdS coating. Submicrosecond to millisecond transient absorption studies were conducted by a home-built transient absorption spectrometer with a Nd/YAG laser (Spectra Physics, Quanta-Ray GCR-11) pumped dye laser (Usho Optical Systems, DL-100, ∼10 ns pulse duration) as a pump source, a 100 W tungsten lamp as a probe source, a photodiode-based detection system (Costronics Electronics), and a TDS-2022 Tektronix oscilloscope . All transient data were collected by confirming identical excitation homogeneity and density of absorbed photons for all samples.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Submicrosecond to millisecond transient absorption studies were conducted by a home-built transient absorption spectrometer with a Nd/YAG laser (Spectra Physics, Quanta-Ray GCR-11) pumped dye laser (Usho Optical Systems, DL-100, ∼10 ns pulse duration) as a pump source, a 100 W tungsten lamp as a probe source, a photodiode-based detection system (Costronics Electronics), and a TDS-2022 Tektronix oscilloscope. 22 All transient data were collected by confirming identical excitation homogeneity and density of absorbed photons for all samples. An excitation wavelength was selected to 425, 480, 500, 515, and 520 nm for CdS-5, -10, -15, -20, and -25/TiO 2 , respectively, shown as arrows in Figure 1 (absorbance: approximately 0.4 after the baseline subtraction).…”
Section: Characterizationmentioning
confidence: 99%
“…The charge separated state at the F1BT2H/TiO 2 or P-F1BT2/TiO 2 interface was monitored by transient absorption spectroscopy. 13 The transient spectrum obtained for P-F1BT2/TiO 2 was further analyzed by comparing the polymer cation spectra generated with the spectroelectrochemical method (see ESIw). 14 The spectrum obtained by applying +0.7 V vs. Ag/AgCl to P-F1BT2/TiO 2 is almost identical with the P-F1BT2/TiO 2 transient spectrum, as shown in Fig.…”
mentioning
confidence: 99%
“…We further demonstrated that the interfacial structural control is the key to function the device by transient absorption spectroscopy. 2 In this presentation, we attempt to verify novel functions of the nanohybrid films by applying to photoelectrochromic devices. A model system as in Fig 2 is considered.…”
mentioning
confidence: 99%